Japanese Mothers’ Intention to HPV Vaccinate Their Daughters: How Has It Changed over Time Because of the Prolonged Suspension of the Governmental Recommendation? - Asami Yagi; Yutaka Ueda; Tatsuo Masuda; Sayaka Ikeda; Takashi Miyatake; Satoshi Nakagawa; Kei Hirai; Tomio Nakayama; Etsuko Miyagi; Takayuki Enomoto; Tadashi Kimura (Vaccines, 2020)
The trend for cervical cancer in younger women has been increasing recently in Japan. However, as a result of the suspension of governmental recommendation, Japan’s HPV (human papillomavirus) vaccination rate for girls born since 2000 has dropped sharply. We conducted an internet survey in December of 2019, 76 months after the suspension of recommendation, to verify the intention of mothers to inoculate their daughter under current circumstances and compared with our previous surveys and leaflet intervention effect. The rates of mothers who replied that they would “inoculate” were significantly higher at 9 and 23 months, but by 32 months after the suspension the rate was significantly lower (p < 0.05, p < 0.05, p < 0.05, respectively). The rates of the mothers who replied they would not inoculate were significantly lower at 9 months and 23 months, but at 76 months was significantly higher (p < 0.05, p < 0.05, p < 0.05, respectively). We found that intervention with a leaflet that could be used under the current suspension of the governmental recommendation did not increase the mothers’ intention to inoculate their daughters. A leaflet that actively encourages vaccination may increase the intent of vaccination. It is strongly recommended that the MHLW promptly resume its recommendations for HPV vaccination.